Telepresence and Sexuality: A Review and a Call to Scholars - Lombard, Matthew; Jones, Matthew (Human Technology, 2013)
Scholars have examined the phenomenon of telepresence, a perceptual illusion of nonmediation experienced by media users, in a wide variety of contexts. This paper explores telepresence theory and research in the rarely examined but important context of sexually arousing media content. After defining key concepts, the paper presents reasons scholars should study telepresence in the context of sexuality, reviews the evolution of relevant media technologies and the nature of relevant telepresence responses, and considers potential theoretical contributions and avenues for future research in interpersonal communication, media studies, and presence scholarship.